A kind of needle-shaped mullite porous ceramic material and preparation method

Through the combination of needle-shaped watery kaolin and hexagonal sheet aluminum hydroxide powder, vacuum extrusion molding technology is used to solve the problems of large thermal expansion coefficient and poor thermal shock resistance of mullite ceramic materials, achieving high efficiency and low cost The preparation process improves the strength and thermal conductivity of the ceramics and is suitable for a variety of high-demand applications.

CN118993710BActive Publication Date: 2025-01-07SHANDONG AOFU ENVIRONMENTAL PROTECTION SCI & TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411495381.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing mullite ceramic materials have a large thermal expansion coefficient and poor thermal shock resistance, and there are problems of high pollution and high cost during the production process.

Method used

The mud material with needle-shaped water kaolin and hexagonal sheet-shaped aluminum hydroxide powder is the main components. It is processed through dry and wet mixing, and after vacuum training, it is plastic extruded to control the sintering temperature and speed to form a needle-shaped mule. Stone porous ceramic material.

Benefits of technology

It realizes a low-cost and environmentally friendly preparation process, improves the strength, heat impact resistance and thermal conductivity of the ceramics, and the pore density can reach 10,000-80,000 cpsi, which is suitable for a variety of high-demand application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993710B_ABST
    Figure CN118993710B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of mullite ceramics, and in particular to a needle-shaped mullite porous ceramic material and a preparation method thereof. The ceramic material is prepared by using a mud material, the mud material comprises an inorganic component, the inorganic component comprises a needle-shaped halloysite and a hexagonal flaky aluminum hydroxide powder; the needle-shaped halloysite comprises kaolinite, the particle size of the kaolinite is less than or equal to 1 μm; the particle size D of the hexagonal flaky aluminum hydroxide powder is 50 The diameter is 1-8 μm, and the diameter-to-thickness ratio is greater than or equal to 20:1. The clay material of this method has good plasticity and flow, and reduces the extrusion pressure; the method has low cost, good effect, and is easy to promote; the material has high pore density and can withstand corrosive environments, cracking, melting, cracking, and reduced specific surface area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mullite ceramics, in particular to a needle-shaped mullite porous ceramic material and a preparation method thereof. Background Art

[0002] Porous ceramics have the characteristics of ultra-high geometric surface area and are widely used in a wide range of applications. It can be used for contact and exchange between gas and gas, gas and liquid, gas and solid, and liquid and solid. Moreover, with the development of new technologies and new energy sources, there is an increasing need for contact and exchange in places with larger geometric surface areas, such as various ultra-high channel microreactors used in the pharmaceutical industry, environmental protection, fuel cells, thermoacoustic refrigeration, thermoacoustic power generation, etc. Due to the wide range of application industries and application scenarios, it is expected that the microreactor will withstand a corrosive exhaust environment for a long time. At the same time, it is expected that the microreactor will withstand more than thousands of cycles of thermal cycles (i.e., cracking, melting, cracking, reduction in specific surface area, or a combination thereof), during which the local temperature can reach up to 1400°C.

[0003] Mullite is a cost-effective material that can withstand corrosive exhaust environments for a long time. According to the relationship that the thermal shock temperature (TST) is inversely proportional to the thermal expansion coefficient (CTE), the elastic modulus (EMOD) is inversely proportional to the strength, due to its relatively high thermal expansion coefficient, it can reach [25-800℃]4.8×10 -6 In order to meet the requirements of high thermal shock performance, the strength of mullite ceramics needs to be improved.

[0004] In conventional technology, densification is generally used to improve the strength of mullite ceramics, but as the ceramics are densified, the strength increases and the elastic modulus also increases. Mullite ceramics can also be formed into a large number of porous, interconnected needle-like crystals, which can toughen mullite ceramics, increase ceramic strength, and improve thermal shock resistance. At the same time, the porous structure ensures a small elastic modulus of mullite ceramics.

[0005]

[0006] Currently, the best method for preparing porous ceramics is to use plastic extrusion molding. However, as the pore density of porous ceramics increases and the wall thickness decreases, plastic extrusion becomes more and more difficult, the extrusion pressure required by the extrusion equipment increases rapidly, and the mud flow performance requirements become higher and higher. The current mass production capacity of porous ceramics prepared by plastic extrusion molding is 900cpsi, the wall thickness is 50.8μm, and the molding extrusion pressure has reached ≥18MPa.

[0007] The current technology for preparing porous needle-shaped mullite ceramics, such as patent CN101164965B, starts with a "green body" containing aluminum and silicon atomic sources. By heating in the presence of a fluorine source, a fluorotopaz compound with a (theoretical) empirical formula of Al2(SiO4)F2 can be formed. The fluorotopaz compound can then be thermally decomposed to form mullite. This method is costly due to the use of SiF4 vapor, and SiF4 vapor is easily hydrolyzed to form hydrofluoric acid, causing environmental pollution.

[0008] For example, patent CN 116535231A requires the addition of a mullite whisker catalyst in advance, and high-temperature sintering allows the whisker catalyst to promote the growth of secondary mullite whiskers. This method requires high-temperature sintering to promote the growth of secondary mullite, with high sintering temperatures and high costs. At the same time, the whisker catalyst forms a large amount of glass phase, and mullite ceramics have a large thermal expansion coefficient and poor thermal shock resistance. Summary of the invention

[0009] The technical problem to be solved by the present invention is to provide a needle-shaped mullite porous ceramic material and a preparation method to solve the problems of large thermal expansion coefficient, poor thermal shock resistance, large pollution in the production process and high cost of mullite ceramics in the prior art.

[0010] The technical solution of the present invention to solve the above technical problems is as follows:

[0011] The present invention provides a method for preparing a needle-shaped mullite porous ceramic material. The ceramic material is prepared by using a mud material. The mud material comprises an inorganic component, and the inorganic component comprises needle-shaped halloysite and hexagonal flaky aluminum hydroxide powder.

[0012] Wherein, the needle-shaped halloysite includes kaolinite, and the particle size of the kaolinite is less than or equal to 1 μm;

[0013] The particle size D of the hexagonal flaky aluminum hydroxide powder 50 The diameter of the nanostructured carbon fiber is 1-8 μm, the diameter-to-thickness ratio is greater than or equal to 20:1, the mass percentage of aluminum oxide is greater than or equal to 64.0%, and the total mass percentage of K2O and Na2O is less than or equal to 0.5%.

[0014] Based on the above technical solution, the present invention can also be improved as follows.

[0015] Furthermore, the particle size D of the needle-shaped halloysite is 50 The diameter of the nanostructured carbon steel is 0.5-2.0 μm, the diameter-to-thickness ratio is greater than or equal to 20:1, the mass percentage of silicon dioxide is greater than or equal to 46%, the mass percentage of aluminum oxide is greater than or equal to 38.0%, and the total mass percentage of K2O and Na2O is less than or equal to 0.5%.

[0016] Furthermore, the mud material also includes a binder, a lubricant and water.

[0017] Furthermore, in the inorganic component, the mass percentage of each component is: the needle-shaped halloysite is 44.68%-45.59%, and the hexagonal flaky aluminum hydroxide powder is 54.41%-55.95%; based on the mass of the inorganic component as 100%, the binder is 5.0%-9%, the lubricant is 1.0%-5.0%, and the mass percentage of water is 29.5%-32%.

[0018] Furthermore, the binder is low-viscosity carboxymethyl cellulose ammonium, and the lubricant is polyethylene glycol oleate or glycerol fatty acid ester.

[0019] Further, the following steps are included:

[0020] S1, dry-mixing the needle-shaped halloysite, the hexagonal flaky aluminum hydroxide powder and a binder, and then wet-mixing and kneading with a lubricant and water to obtain the mud material;

[0021] S2, refining the clay material under vacuum conditions to obtain a clay segment;

[0022] S3, extruding the mud segments and preparing them into a honeycomb structure, and then drying, cutting, sintering, and cold processing them in sequence to obtain the needle-shaped mullite porous ceramic material.

[0023] Further, in step S2, the vacuum degree of the vacuum condition is greater than or equal to -0.09 MPa.

[0024] Further, in step S3, the extrusion pressure is 4-8 MPa.

[0025] Further, in step S3, the calcination includes a stage of aluminum hydroxide losing crystal water, a stage of kaolin losing crystal water, a stage of mullite crystal formation and a heat preservation stage;

[0026] The temperature of the aluminum hydroxide losing crystal water stage is 200-400°C, and the heating rate is 5-10°C / hour;

[0027] The temperature of the kaolin during the stage of losing crystal water is 450-600°C, and the heating rate is 10-30°C / hour;

[0028] The temperature of the mullite crystal forming stage is 1200° C., and the heating rate is 5-20° C. / hour; the temperature of the heat preservation stage is 1250-1350° C., and the heat preservation time is 4-8 hours.

[0029] The present invention also provides a needle-shaped mullite porous ceramic material, which is prepared by the above method. The porous ceramic material has a pore density of 10000-80000 cpsi and a wall thickness of 1-2 mil.

[0030] The beneficial effects of the present invention are:

[0031] (1) The method for preparing the needle-shaped mullite porous ceramic material of the present invention comprises: the needle-shaped halloysite has very fine kaolinite, which has very good plasticity and fluidity after being hydrated, and can reduce the extrusion pressure of the mud material; the fine kaolinite is very easy to form mullite under low-temperature sintering, and the needle-shaped structure is very easy to be oriented in the process of plastic extrusion molding; during sintering, the mullite crystals grow along the oriented needle-shaped halloysite to form a needle-shaped mullite structure;

[0032] (2) In the preparation method of the needle-shaped mullite porous ceramic material of the present invention, the flake aluminum hydroxide can not only further reduce the extrusion pressure of the mud material, but also decompose into a highly active aluminum oxide transition phase during the sintering process, which is beneficial to the growth and development of mullite crystals;

[0033] (3) The method for preparing the needle-shaped mullite porous ceramic material of the present invention has good mud fluidity, low extrusion pressure during the preparation process, and no components that cause environmental pollution are used during the preparation process. It has low cost, good effect, and is easy to promote;

[0034] (4) The needle-shaped mullite porous ceramic material of the present invention has high strength, high thermal shock resistance and high thermal conductivity;

[0035] (5) The needle-shaped mullite porous ceramic material of the present invention has a pore density of 10000 cpsi-80000 cpsi, a wall thickness of 1-2 mil, and a geometric specific surface area of ​​125.98 cm 2 / cm 3 -319.44cm 2 / cm 3 ;

[0036] (6) The needle-shaped mullite porous ceramic material of the present invention can be widely used in various fields to meet the requirements of environments such as withstanding corrosion, cracking, melting, cracking, and reduction of specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The preparation method of the needle-shaped mullite porous ceramic material of the present invention, the SEM image of the needle-shaped halloysite;

[0038] Figure 2The preparation method of the needle-shaped mullite porous ceramic material of the present invention, the SEM image of hexagonal flake aluminum hydroxide;

[0039] Figure 3 The preparation method of the needle-shaped mullite porous ceramic material of the present invention, the SEM image of the material of Example 6;

[0040] Figure 4 This is a method for preparing the needle-shaped mullite porous ceramic material of the present invention, and a local enlarged SEM image of the crystal in the material of Example 6. DETAILED DESCRIPTION

[0041] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0042] The invention discloses a method for preparing a needle-shaped mullite porous ceramic material. The ceramic material is prepared by using a mud material. The mud material comprises an inorganic component, and the inorganic component comprises a needle-shaped halloysite and a hexagonal flaky aluminum hydroxide powder. The needle-shaped halloysite comprises kaolinite, and the particle size of the kaolinite is less than or equal to 1 μm. The particle size of the hexagonal flaky aluminum hydroxide powder is D 50 The diameter of the nanostructured carbon fiber is 1-8 μm, the diameter-to-thickness ratio is greater than or equal to 20:1, the mass percentage of aluminum oxide is greater than or equal to 64.0%, and the total mass percentage of K2O and Na2O is less than or equal to 0.5%.

[0043] The preparation method of the needle-shaped mullite porous ceramic material of the present invention uses needle-shaped halloysite, which has very fine (≤1μm) kaolinite. After the fine kaolinite is hydrated, it has very good plasticity and fluidity, can improve the plasticity and fluidity of the mud material, and reduce the extrusion pressure; at the same time, the fine kaolinite is very easy to form mullite under low-temperature sintering conditions, and the needle-shaped structure is very easy to be oriented in the process of plastic extrusion molding. During sintering, the mullite crystal grows along the oriented needle-shaped halloysite to form a needle-shaped mullite structure; the flake aluminum hydroxide can also effectively improve the plasticity and fluidity of the mud material due to its hexagonal flake structure (diameter-to-thickness ratio ≥10), and the aluminum hydroxide is decomposed into a highly active aluminum oxide transition phase during the sintering process, which is beneficial to the growth and development of the mullite crystal.

[0044] In addition, in the present invention, the K2O and Na2O contents in the hexagonal flaky aluminum hydroxide powder can avoid the problem of easy formation of glass phase due to excessively high K2O and Na2O contents. At the same time, excessively high K2O and Na2O contents will also increase the thermal expansion coefficient of mullite ceramics and reduce acid and alkali resistance.

[0045] The microstructures of the needle-shaped halloysite and hexagonal flaky aluminum hydroxide used in the present invention are as follows: Figure 1 and Figure 2 shown.

[0046] Preferably, the particle size D of the needle-shaped halloysite is 50 The particle size and diameter-thickness ratio of the needle-shaped halloysite, as well as the specific component content, help to reduce the extrusion pressure and can better form mullite crystals during sintering, thereby further effectively improving the thermal shock resistance and thermal conductivity of the material.

[0047] Preferably, the mud also includes a binder, a lubricant and water.

[0048] Further preferably, the binder is low-viscosity ammonium carboxymethyl cellulose with a viscosity of 400-1000mPa.s (2% aqueous solution, 20°C). Using water-soluble ammonium carboxymethyl cellulose as a binder can effectively increase the plasticity of the mud, and ammonium methyl cellulose does not contain alkali metals and alkaline earth metals, which is beneficial to the thermal expansion coefficient of mullite ceramics.

[0049] Further preferably, the lubricant is a water-emulsifiable oleic acid ester or fatty acid ester substance, so that the particles after emulsification can reach tens of nanometers and can be filled between the raw material particles to play a lubricating role, improve the fluidity of the mud, and reduce the extrusion pressure.

[0050] More preferably, the lubricant is polyethylene glycol oleate or glycerol fatty acid ester.

[0051] More preferably, the lubricant is polyethylene glycol oleate, the acid value of polyethylene glycol oleate is ≤10 mgKOH / g, the saponification value is ≥60 mgKOH / g, and the net content is ≥99%.

[0052] Preferably, in the inorganic component, the mass percentage of each component is: acicular halloysite is 44.68%-45.59%, hexagonal flaky aluminum hydroxide powder is 54.41%-55.95%; based on the mass of the inorganic component as 100%, low-viscosity ammonium carboxymethyl cellulose is 5.0%-9%, polyethylene glycol oleate is 1.0%-5.0%, and the mass percentage of water is 29.5%-32%.

[0053] Preferably, the method of the present invention comprises the following steps:

[0054] S1. Dry-mix needle-shaped halloysite, hexagonal aluminum hydroxide powder and binder. Dry-mixing can be done by using an inclined weightless mixer. The strong stirring time is 0.5-1 hour. Then wet-mix and knead with lubricant and water. The wet kneading time is 1-2 hours to obtain mud.

[0055] S2. The clay material is refined under vacuum conditions to obtain clay segments with plasticity.

[0056] Preferably, the vacuum degree of the vacuum condition is greater than or equal to -0.09 MPa.

[0057] S3, extruding the mud segments and preparing them into a honeycomb structure, and then drying, cutting, sintering, and cold processing them in sequence to obtain a needle-shaped mullite porous ceramic material.

[0058] Preferably, the drying method is microwave drying.

[0059] Preferably, the extrusion pressure is 4-8 MPa.

[0060] In the steps of the present invention, in order to prevent cracking during firing and improve the qualified rate, the firing temperature and heating rate need to be controlled. Specifically, the firing includes a stage where aluminum hydroxide loses crystal water, a stage where kaolin loses crystal water, a stage where mullite crystals form, and a stage where they are kept warm.

[0061] The temperature in the stage where aluminum hydroxide loses its crystal water is 200-400°C. Since aluminum hydroxide has relatively more crystal water, the temperature needs to be slowly increased in this stage, with a heating rate of 5-10°C / hour.

[0062] The temperature of kaolin losing crystal water is 450-600°C, and the heating rate of this stage is also relatively slow, but it is greater than the heating rate of aluminum hydroxide losing crystal water, specifically 10-30°C / hour.

[0063] The temperature of the mullite crystal formation stage is 1200℃. In order to make the crystal grow better, the heating rate in this stage also needs to be controlled not to be too high. Therefore, the heating rate in this stage is 5-20℃ / hour; the temperature of the insulation stage is 1250-1350℃, and the insulation time is 4-8 hours.

[0064] The needle-shaped mullite porous ceramic material of the present invention is prepared by the above-mentioned method.

[0065] The porous ceramic material of the present invention is for various microreactors requiring ultra-high geometric specific surface area, such as the pharmaceutical industry, environmental protection, fuel cells, thermoacoustic refrigeration, thermoacoustic power generation, etc. The ceramic material has a diameter of 1-13 inches, a height of 2-12 inches, a pore density of 10000-80000 cpsi, and a wall thickness of 1-2 mil.

[0066] There is no particular restriction on the shape of the honeycomb grid in the honeycomb structure. A single hole shape such as triangle, square, hexagon, etc. can be used, or multiple hole shapes such as square, hexagon, asymmetric, etc. can be used. It is not necessary to use a single hole shape in the honeycomb structure, and it is preferred to use, for example, square holes.

[0067] The present invention is illustrated below by means of specific examples.

[0068] Examples 1 to 9 are needle-shaped mullite porous ceramic materials prepared by the method of the present invention. Table 1 shows the shape parameters of each component in the mud material of each example, the needle-shaped halloysite includes needle-shaped halloysite K1, needle-shaped halloysite K2, and needle-shaped halloysite K31, and the hexagonal flaky aluminum hydroxide powder includes flaky aluminum hydroxide A1, flaky aluminum hydroxide A2, and flaky aluminum hydroxide A3.

[0069] The comparative example is prepared by using common mullite with 70% aluminum content, 10% high viscosity (6000-10000mPa.s) HPMC, and 6% soybean oil or tung oil, and its specific sintering method is the same as that of the present invention.

[0070] Table 2 shows the mass percentages of the specific components of each embodiment. The mass of the inorganic component (acicular halloysite, hexagonal flaky aluminum hydroxide powder) is 100%, the binder is ACMC, the lubricant is polyethylene glycol oleate, and the mass percentages of the binder, lubricant and water are all weight parts calculated in addition to the total weight of the inorganic components. The morphology of the needle-shaped mullite porous ceramic material prepared in Example 6 is shown in FIG. Figure 3 and 4 Table 3 is a comparison of the material properties of Examples 1 to 9 and the comparative example.

[0071] Table 1 Shape parameters of inorganic components used in Examples 1 to 9

[0072]

[0073] Table 2 Mass percentage of specific components in each embodiment

[0074]

[0075] Table 3 Comparison of material properties of Examples 1 to 9 and Comparative Examples

[0076]

[0077] It can be seen from Examples 1-9 that as the diameter-to-thickness ratio of needle-shaped halloysite and the diameter-to-thickness ratio of hexagonal flake aluminum hydroxide increase, the mud flowability becomes better and the extrusion pressure decreases. As the pore density increases and the wall thickness decreases, the extrusion pressure increases, but all can be satisfied at 4-8MPa.

[0078] As the pore density increases and the wall thickness decreases, the extrusion qualified rate shows a downward trend, but it can reach more than 98%, which is much higher than the 95.72% of the control example; at the same time, as the diameter-to-thickness ratio of the needle-shaped halloysite and the diameter-to-thickness ratio of the hexagonal flake aluminum hydroxide increase, the strength increases, and the thermal shock resistance also improves. The reason is that as the diameter-to-thickness ratio of the raw material increases, the directional arrangement of the raw material becomes more orderly, the directional arrangement of the needle-shaped mullite crystals becomes better, the strength increases accordingly, and the thermal shock resistance also becomes better.

[0079] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A method for preparing a needle-shaped mullite porous ceramic material, characterized in that: The ceramic material is prepared by using clay, and the clay comprises inorganic components, and the inorganic components are composed of needle-shaped halloysite and hexagonal flaky aluminum hydroxide powder; Wherein, the needle-shaped halloysite includes kaolinite, and the particle size of the kaolinite is less than or equal to 1 μm; The particle size D of the hexagonal flaky aluminum hydroxide powder 50 1-8μm, diameter-to-thickness ratio greater than or equal to 20:1, mass percentage of aluminum oxide greater than or equal to 64.0%, total mass percentage of K2O and Na2O less than or equal to 0.5%; In the inorganic component, the mass percentage of each component is: the needle-shaped halloysite is 44.68%-45.59%, and the hexagonal flaky aluminum hydroxide powder is 54.41%-55.95%; The needle-shaped mullite porous ceramic material is formed by extrusion, and the extrusion pressure is 4-8MPa; The sintering of the needle-shaped mullite porous ceramic material includes a stage where aluminum hydroxide loses crystal water, a stage where kaolin loses crystal water, a stage where mullite crystals form, and a stage where heat is kept warm. The temperature of the aluminum hydroxide losing crystal water stage is 200-400°C, and the heating rate is 5-10°C / hour; The temperature of the kaolin during the stage of losing crystal water is 450-600°C, and the heating rate is 10-30°C / hour; The temperature of the mullite crystal forming stage is 1200° C., and the heating rate is 5-20° C. / hour; the temperature of the heat preservation stage is 1250-1350° C., and the heat preservation time is 4-8 hours.

2. The method for preparing a needle-shaped mullite porous ceramic material according to claim 1, characterized in that: The particle size D of the needle-shaped halloysite 50 The diameter of the nanostructured carbon steel is 0.5-2.0 μm, the diameter-to-thickness ratio is greater than or equal to 20:1, the mass percentage of silicon dioxide is greater than or equal to 46%, the mass percentage of aluminum oxide is greater than or equal to 38.0%, and the total mass percentage of K2O and Na2O is less than or equal to 0.5%.

3. The method for preparing a needle-shaped mullite porous ceramic material according to claim 2, characterized in that: The mud material also includes a binder, a lubricant and water.

4. The method for preparing a needle-shaped mullite porous ceramic material according to claim 3, characterized in that: Based on the mass percentage of the inorganic component being 100%, the mass percentage of the binder is 5.0%-9%, the mass percentage of the lubricant is 1.0%-5.0%, and the mass percentage of water is 29.5%-32%.

5. The method for preparing a needle-shaped mullite porous ceramic material according to claim 4, characterized in that: The binder is low-viscosity carboxymethyl cellulose ammonium, and the lubricant is polyethylene glycol oleate or glycerol fatty acid ester.

6. The method for preparing a needle-shaped mullite porous ceramic material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, dry-mixing the needle-shaped halloysite, the hexagonal flaky aluminum hydroxide powder and a binder, and then wet-mixing and kneading with a lubricant and water to obtain the mud material; S2, refining the clay material under vacuum conditions to obtain a clay segment; S3, extruding the mud segments and preparing them into a honeycomb structure, and then drying, cutting, sintering, and cold processing them in sequence to obtain the needle-shaped mullite porous ceramic material.

7. The method for preparing a needle-shaped mullite porous ceramic material according to claim 6, characterized in that: In step S2, the vacuum degree of the vacuum condition is greater than or equal to -0.09 MPa.

8. A needle-shaped mullite porous ceramic material, characterized in that: The porous ceramic material is prepared by the method according to any one of claims 1 to 7, wherein the pore density of the porous ceramic material is 10,000-80,000 cpsi and the wall thickness is 1-2 mil.

Citation Information

Patent Citations

  • Porous mullite bodies and methods of forming them

    CN101164965B

  • Method for preparing porzite porous honeycomb ceramic with needle-shaped crystal structure

    CN101781124A

  • Particle filter and preparation method thereof

    CN113387694A